(In)security in Post-Soviet Eurasia: Contributions from Critical Security Studies - Simão, Licínia (2013)
Since the 1990s, (in)security in post-Soviet Eurasia has been conceptualized by International Relations scholars as being mainly connected to the permanence of regional violent conflicts and the challenges of fragile sovereignty. After 9/11, terrorism as a broad category has also been added to the lexicon. These views place state security at the centre of analysis, and focus mainly on military aspects of security. This article addresses the limitations of analyses of post-Soviet Eurasian security shaped by these two trends and puts forwards critical alternatives to analyse insecurity in this region. Building on insights from critical security studies, namely Ken Booth’s work and his central concept of emancipation, as well as the nexus between human rights and security – human security –, this paper presents a new framework of analysis for regional (in)security in post-Soviet Eurasia. The main goal is to reflect on the innovative aspects of this approach in terms of understanding increasingly complex (in)security dynamics in this region, and overcome what have been mainly realist and realpolitik views of regional security.